Welding Technologies Special topic volume with invited peer-reviewed papers only - Ionescu, Mihail; Chandra, Tara; Sommitsch, Christof; Shabadi, Raj (Trans Tech Publications Ltd, 2023)
This special issue is fully dedicated to the recent achievements in the development of modern welding technologies and will be helpful to a wide range of specialists in the field of modern machinery. Welding, Steel, Alloy, Laser Welding, Resistance Spot Welding, Friction Stir Welding, Mechanical Properties, Phase Transformations, Heat Treatment, Dissimilar Lap Joints, Ultrasonic Bonding, Heat Affected Zone, Microalloying, Seam Weld, Explosive Welding Materials Science, Manufacturing.
Keywords: elektronické knihy; electronic books